Effects of Mushroom Baglog-Based Liquid Organic Fertilizer on Pakcoy Growth - Putri, Galuh_Septiani; Icha Saldela Martiana; Putri Tasya Wulandari; Ananda Zulaikai (Talenta Publisher, 2024)
Liquid organic fertilizer is an important type of organic fertilizer that can improve soil structure and provide additional nutrients. Liquid Organic Fertilizer (LOF) has several advantages over other fertilizers, including ease of production, long-chain nutrient release, facilitation of photosynthesis, increased nutrient content, and improved soil growth. Organic fertilizers are commonly used in agriculture, especially on cultivated lands. Organic waste is a by-product of non-economic production processes. This study was conducted at Muhammadiyah University of Surakarta, specifically in the greenhouse, over a period of 28 days, from November 29, 2023, to December 27, 2023. A Randomized Complete Block Design (RCBD) was used as the basis for the experiment. For liquid organic fertilizer concentration, three treatments were applied to plants in three pots, each containing two Pakcoy plants (Brassica rapa L.), with LOF irrigation given every nine days. The first treatment served as a control with no LOF application, while the second treatment involved the application of 1 milliliter of LOF diluted in 500 milliliters of water.